EVALUASI MUTU SELAI SALAK (Salacca sumatrana B.) DENGAN PENAMBAHAN KELOPAK BUNGA ROSELA MERAH (Hibiscus sabdariffa L.) - Putra Yuli; Yusmarini Yusmarini; Faizah Hamzah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this research was to discover the effect of roselle augmentation to quality of zalacca jam and to inquire the interest of panelist's on the profit results. The research was carried out experimentally using Complete Randomized Design (CRD) by five treatments and four replications. The treatments were SR0 (zalacca pulp 100%), SR1 (zalacca pulp 90% and roselle pulp 10%), SR2 (zalacca pulp 80% and roselle pulp 20%), SR3 (zalacca pulp 70% and roselle pulp 30%), and SR4 (zalacca pulp 60% and roselle pulp 30%). The obtained data were analyzed statistically by Analysis of Variance (ANOVA) and followed by Duncan’s New Multiple Range Test (DNMRT) at 5% stage. The results showed that the augmentation of zalacca fruit and roselle had significantly influenced the level of acidity (pH), water content, ash content, fiber content, the amount of dissolved solids and organoleptic test. The best treatment of this research was SR2 which had degree acidity (pH) 3.52, water content 25.45%, ash content 0.75%, fiber content 8.46%, amount of dissolved solids of 79.52ºBrix, and was described as red coloured, zalacca and roselle flavoured, sour taste, soft texture and the most preferred by the panelist’s to overall assessment. Keywords: jam, zalacca fruit and roselle calyx